PENGARUH EKSTRAK AKAR TANAMAN KUCING- KUCINGAN (ACALYPHA INDICA L.) ASAL KOTA KUPANG TERHADAP PERTUMBUHAN STAPHYLOCOCCUS AUREUS - Ernesta Dje, Maria; Nikmah; Surianty Ardan, Andam; Kopong Tokan, Moses (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Nosocomial infections caused by Staphylococcus aureus are increasing and have become a serious problem because this bacterium can grow rapidly and is difficult to treat. The use of medicinal plants as alternative therapies has therefore gained attention, one of which is kucing-kucingan (Acalypha indica L.). This study aimed to analyze the effect of kucing-kucingan (Acalypha indica L.) root extract on the growth of Staphylococcus aureus and to determine the concentration of root extract from Kupang City that can inhibit and kill Staphylococcus aureus. The method used was a laboratory experimental design employing the dilution method to determine the MIC (Minimum Inhibitory Concentration) and MBC (Minimum Bactericidal Concentration), with each treatment performed in triplicate. The concentrations of kucing-kucingan (Acalypha indica L.) root extract used were 300 mg/mL, 600 mg/mL, and 900 mg/mL. Sterile distilled water was used as the control. The results showed that higher concentrations of kucing-kucingan (Acalypha indica L.) root extract resulted in greater inhibition of Staphylococcus aureus growth. The MIC was observed at the lowest concentration, 300 mg/mL, with Staphylococcus aureus growth of 156,33 CFU, while at the highest concentration, 900 mg/mL, bacterial growth decreased to 67,66 CFU. In this study, no MBC activity of kucing-kucingan (Acalypha indica L.) root extract was observed. Thus, kucing-kucingan (Acalypha indica L.) root extract has potential as a natural antibacterial alternative for nosocomial infections caused by Staphylococcus aureus.